Quality of Life in Patients with Biologically Controlled Primary Hypothyroidism: Assessment and Relationship with TSH Level - BEL HADJ SLIMAN, Chaima; Yazidi, Meriem; Ibtissem, Oueslati; Lina, Ghram; KHESSAIRI, Nadia; CHAKER, Fatma; CHIHAOUI, Melika (Jordan Medical Journal, 2025)
Some biologically well-controlled patients with primary hypothyroidism (PH) report persistent symptoms which can impact their quality of life (QoL). The aim of this study was to evaluate the QoL of patients with biologically controlled PH, and to determine the cutoff value of TSH associated with a better QoL. Methods: This was a cross-sectional study including 70 adult patients with biologically controlled PH (TSH in the normal range). QoL was assessed by the SF36 questionnaire and treatment adherence was assessed by the Girerd questionnaire. Results: The patients mean age was 51.2±9.6 years and the sex ratio (Men/Women) was 0.08. The mean duration of hypothyroidism was 8.4±6.7 years and the mean TSH level was 2.29±0.92mIU/L [0.62–4.25]. The mean value of the overall SF36 score was 61.11±23.8%. QoL was good in 53% of cases and impaired in 47% of cases. The altered items were related to physical state, perceived health, vitality, and psychological health. The TSH value at the time of the study was the only factor associated with impaired QoL (2.55±0.97 vs 2.05±0.80 mIU/L; p=0.024). A TSH>2.45mIU/L was the cutoff value associated with impaired QoL (p=0.015). After multivariate analysis, a TSH level > 2.45 mIU/L remained the only factor independently associated with impaired QoL. Conclusions: Nearly half of patients with biologically controlled PH had impaired QoL. A TSH between 0.4 and 2.45 mUI/L is the target value to be achieved by the replacement therapy to improve the QoL of these patients.